Attack the block [videorecording (DVD)] - Cornish, Joe, 1968-; Whittaker, Jodie, 1982-; Boyega, John; Esmail, Alex; Townend, Tom; Treadaway, Luke, 1984-; Frost, Nick, 1970- (Sony Pictures Home Entertainment, 2011)
A gang of tough inner-city kids try to defend their turf against an invasion of savage alien creatures, which turns a South London apartment complex into an extraterrestrial warzone.